Income of Micro, Small, And Medium Enterprises With The Presence of A Mini Market In Palopo City, Indonesia - Mujahidin Mujahidin; Fasiha Fasiha; Muh. Ruslan Abdullah; Maya Praseta (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2022)
This study Discusses the Income of Micro, Small, and Medium Enterprises before and after the presence of the Mini Market, this research aims to describe the income of micro, small and medium enterprises, the method used is a descriptive qualitative research method and the data sources used are primary data through field studies (field research) and secondary data through library research with data collection techniques through observation, interviews, and documentation, as for data analysis techniques through three stages, namely data reduction, data presentation, and conclusion drawing. Based on the results of research conducted that the income of UMKM after the presence of mini markets has decreased, it can be seen from 9 business actors, 7 of which experienced a decrease in income with an average decrease of 53.75% while 2 business actors experienced an increase in income with an average of 43.75%. for this reason, the solution provided by the government is that UMKM must improve the service and availability of merchandise, with efforts to provide business capital and increase the capacity of human resources for UMKM actors by holding training and education programs from the Palopo City government.